Hubungan status gizi dengan tekanan darah pada siswa SD Katolik RK IV Santo Yohanes Manado - Mantik, Keren E.K.; Umboh, Adrian; Wilar, Rocky (Universitas Sam Ratulangi, 2016)
Abstract: Nutritional status problems such as undernutrition and overnutrition are still widespread in Indonesia. Nutritional status, notably overnutrition, may result in increased blood pressure through the mechanisms of increased leptin, insulin resistance, increased free fatty acids, and activation of the renin-angiotensin-aldosterone system. This study was aimed to determine the relationship between nutritional status and blood pressure (systolic and diastolic) in Santo Yohanes IV Catholic Elementary School students. This was an observational analytical study with a cross-sectional design. Sampling was conducted among students at Santo Yohanes IV Catholic Elementary School from August 2016 until November 2016 using consecutive sampling method. Total samples were 152 students.. The chi-square test showed that there was a relationship between nutritional status and systolic as well as diastolic blood pressure (p=0.003). The Spearman correlation test concerning nutritional status with systolic and diastolic blood pressure showed the r values of 0.321 and 0.319, respectively. Conclusion: There was a significant relationship between nutritional status and blood pressure (systolic and diastolic) in school-aged children, however, overweight and obese children had higher risks of elevated blood pressure (systolic and diastolic).Keywords: nutrirional status, blood pressure, school-aged childrenÂ Abstrak: Masalah status gizi seperti gizi kurang dan gizi lebih masih tersebar luas di Indonesia. Status gizi terutama gizi lebih dapat berdampak pada meningkatnya tekanan darah melalui mekanisme peningkatan kadar leptin, resistensi insulin, peningkatan kadar asam lemak bebas, dan aktivasi sistem renin-angiotensin-aldosteron. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dengan tekanan darah (sistolik dan diastolik) pada siswa SD Katolik RK IV Santo Yohanes Manado. Jenis penelitian ialah survei analitik observasional dengan desain potong lintang. Pengambilan sampel dilakukan di SD Katolik RK IV Santo Yohanes Manado dari bulan Agustus 2016 sampai November 2016 dengan metode consecutive sampling berjumlah 152 siswa. Hasil uji chi-square terhadap status gizi dengan tekanan darah sistolik dan diastolik menunjukkan terdapat hubungan antara status gizi dengan tekanan darah baik sistolik maupun diastolik (p=0,003). Dari uji korelasi Spearman terhadap status gizi dengan tekanan darah sistolik dan diastolik diperoleh nilai r masing-masing yaitu 0,321 dan 0,319. Simpulan: Terdapat hubungan bermakna antara status gizi dengan tekanan darah (sistolik dan diastolik) pada anak usia sekolah. Anak dengan overweight dan obese mempunyai risiko lebih tinggi terhadap peningkatan tekanan darah (sistolik dan diastolik). Kata kunci: status gizi, tekanan darah, anak usia sekolah